Influence of work-family conflict, job demands and resilience on job burnout among employees in healthcare industry - Chan, Wai Kok; Eng, Min Shen; Fong, Weng Khai; Law, Zi Li; Manesha, L Baskaran (2021)
The purpose of this research is to determine the impact of work-family conflict, job demands and resilience on the job burnout among employees in healthcare industry. This study is also used to validate whether the job burnout among employees in healthcare industry are affected by those three independent variables. The research is carried out by distributing 120 online questionnaires to respondents from the targeted locations involving Penang, Kedah, Perak and Selangor. The data retrieved from the from the online surveys will be processed with the aid of Microsoft Excel and Statistical Package for Social Science (SPSS) in order to produce accurate results for the purpose of analysis and interpretation. In this case, the data will be analysed based on reliability test, descriptive analysis, Pearson Correlation and many more. Lastly, work-family conflict, job demands and resilience significantly influences the job burnout among employees in healthcare industry, wherein in the increase in either one of the independent variables will increase the job burnout among employees in healthcare industry. There are a few studies which are consistent with the results, thus it is further elaborated in one of the chapters.